흑연막 전해 박리로 합성된 2차원 그래핀의 전기화학적 물성 - 이승훈 (The Graduate School, Ajou University, 2011)
In graphite and graphitized carbonaceous materials, it is known that they have different Li storage capacity and electrochemical properties depending on the structures. In particular, graphene which have outstanding physical, chemical and electrochemical properties was the most attention for alternative anode material of Li-ion batteries.
학위논문(석사)--아주대학교 일반대학원 :재료공학과,2011. 2
Keywords: Graphene; Secondary Battery; Anode; Electrolytic Exfoliation; 흑연막; 전해 박리